Vesta’s Shape and Morphology - Jaumann, R.; Williams, D.A.; Buczkowski, D.L.; Yingst, R.A.; Preusker, Frank; Hiesinger, H.; Schmedemann, N.; Kneissl, T.; Vincent, J.B.; Blewett, D.; Buratti, B.J.; Carsenty, U.; et al. (Science, 2012)
Vesta’s surface is characterized by abundant impact craters, some with preserved ejecta blankets, large troughs extending around the equatorial region, enigmatic dark material, and widespread mass wasting, but as yet an absence of volcanic features. Abundant steep slopes indicate that impact-generated surface regolith is underlain by bedrock. Dawn observations confirm the large impact basin (Rheasilvia) at Vesta’s south pole and reveal evidence for an earlier, underlying large basin (Veneneia). Vesta’s geology displays morphological features characteristic of the Moon and terrestrial planets as well as those of other asteroids, underscoring Vesta’s unique role as a transitional solar system body.